2015
DOI: 10.5152/turkpediatriars.2015.2827
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of epidemiological and clinical features of influenza and other respiratory viruses

Abstract: Aim: In our study, we aimed to clinically and epidemiologically evaluate respiratory tract infections the viral agents of which were detected by molecular methods and to compare influenza and other respiratory tract viruses in this context. Material and Methods:The records of 178 patients aged above 2 years who presented to pediatric emergency outpatient clinic with fever and respiratory tract infection findings between December 2013 and April 2014 were examined retrospectively. Results: At least one respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
2
18
0
2
Order By: Relevance
“…NLR and PLR are good markers of systemic infection. These ratios have also been confirmed as prognostic and predictive factors in various viral diseases [17,18,19]. A study was conducted in patients with chronic hepatitis B (CHB) [18].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…NLR and PLR are good markers of systemic infection. These ratios have also been confirmed as prognostic and predictive factors in various viral diseases [17,18,19]. A study was conducted in patients with chronic hepatitis B (CHB) [18].…”
Section: Discussionmentioning
confidence: 93%
“…However, rates of neutrophil/lymphocyte were significantly higher at the time of admission to the hospital [23]. The neutrophil/lymphocyte ratio is a practical systemic inflammation indicator and has been studied as a prognostic factor [17,23]. To the best of our knowledge, MPV in patients with influenza infections has not been previously studied.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study Influenza viruses (A and B) was found to be highest (50%) among their patients. RSV was the second leading agent in the 2-5 year age group (35).…”
Section: Discussionmentioning
confidence: 99%